The Malay version of patient activation measure: an instrument for measuring patient engagement in healthcare - Syahnaz Mohd Hashim,; Idayu Badilla Idris,; Shalisah Sharip,; Rafidah Bahari,; Jahan, Nasrin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Effective diabetes management depends on both pharmacological treatment and patients’ engagement in their own care. PAM is an instrument that measures patients’ ability to self-manage their chronic illnesses and determines patients’ level of activation. The purpose of this study was to develop a translated Malay version of the PAM instrument and subsequently, to conduct a reliability and validity assessment. A cross-sectional study among patients with type 2 diabetes was performed in a teaching public primary care clinic. Forward and backward translation was conducted, followed by pre-testing and cognitive interviewing. Data from 130 patients were analysed using SPSS software to assess the internal consistency and the psychometric properties of the Malay version of PAM instrument. Cronbach’s alpha for all items was 0.87, indicating good internal consistency. Exploratory Factor Analysis (EFA) showed a possibility of a three-factor model, which were labelled as a) confidence in performing preventive behaviors b) feel responsible and in charge of own health, and c) knowledge, ability to communicate and adherence to treatment. All items have a factor loading of higher than 0.4. The Cronbach’s alpha value was 0.85, 0.7 and 0.58 for the first, second and third subscales, respectively. The Malay version of PAM instrument showed a good reliability index and might have multiple subscales. Assessing these subscales are useful for the healthcare team in the evaluation of ‘patient activation’ among patients with diabetes. Efforts will thus be easier when responding to the patients’ needs and facilitating them to become active health managers.